DISSOLUTION OF FORSTERITIC OLIVINE AT 65°C AND 2<pH<5 - Chen Y.; Brantley S.L. (My University, 2000)
Dissolution experiments with forsteritic olivine (Fo91) were conducted in a batch reactor at a temperature of 65°C between pH 2 and 5. Constant pH was maintained by using a pH-stat technique. The following dissolution rate law for forsteritic olivine at 65°C and acid pH was derived based on the experimental results normalized to the initial surface area:r=10-8.51(aH+)0.70where r is rate in mol forsteritic olivine/cm2/s. Our results, combined with data from the literature for forsteritic olivine dissolution at 25°C, show that the pH-dependence of forsteritic olivine dissolution is temperature-dependent. As temperature increases, the dissolution rate of forsteritic olivine becomes more pH-dependent, which is consistent with a surface protonation model for dissolution at pH<pHpznpc. The activation energy of dissolution, Ea, has been estimated based on our results and literature data at 30+/-4 kcal/mol. We also observed that at pH between 2 and 4 and at 65°C, the release rates of Mg, Si and Fe were stoichiometric. However, at pH 5, the release rate of Fe was slower than that of Mg and Si, probably due to oxidation of the mineral surface. Results of several dissolution experiments in the presence of Al in solution (pH 3, 0.03-10 ppm Al) show that the dissolution rate of forsteritic olivine under the experimental conditions is independent of Al concentration within the experimental error. This result may indicate that Al does not form strong crosslinks to the unpolymerized surface of orthosilicates such as forsteritic olivine, and therefore does not retard the dissolution of this phase under the experimental conditions.
Keywords: FORSTERITIC OLIVINE; DISSOLUTION KINETICS; SIMPLE OXIDES